Study of wear and friction properties of slip-resistant epoxy floors (Journal of the College of Basic Education, 2022)
In this research, composite materials used in the manufacture of non-slip floorings have been prepared because of this application in places that require high friction while maintaining sufficient mechanical strength and wear resistance, such as floors of swimming pools and car garages. Initially, a base material was made of unreinforced epoxy to be used as a basis for casting, with 4 samples in addition to a pure epoxy sample that is not painted for the purpose of comparison with the painted samples, and after initial hardening for 24 hours, the castings were placed in an oven at 55 ° C for 4 hours to obtain the highest Possible cross-linking ratio. After that, the castings were left for a week at room temperature to get rid of stress and to ensure the best cross-linking was achieved. Anti-slip materials were prepared from coarse and fine broken glass and coarse and fine building aggregate by mixing them with 40% epoxy. On one epoxy sample without coating. These castings were cut according to the standard specifications for each test (wear resistance and coefficient of friction). The results showed that the sample coated with fine glass debris and fine building materials aggregate showed the highest wear resistance compared to the other samples, where the wear rate was (4.25 x 10-9 g/ cm. As for the friction coefficient test, all samples showed a higher friction coefficient than the uncoated epoxy sample, which helps to prevent slipping if the coatings are applied to the floors to enhance the friction, as previously explained in the floors that require this.